2021
DOI: 10.1101/2021.01.25.428066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological habitat partitioning and feeding specialisations of coastal minke whales (Balaenoptera acutorostrata) using a designated MPA in northeast Scotland

Abstract: In the design of protected areas for cetaceans, spatial maps rarely take account of the life-history and behaviour of protected species relevant to their spatial ambit, which may be important when modelling population trends or assessing susceptibility to anthropogenic threats. In the present study, we examined the distribution and feeding behaviours of minke whales by age-class (adults versus juveniles) from long-term studies in the Moray Firth in northeast Scotland, where a Marine Protected Area (MPA) has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Only a small proportion of co-occurrences were attributable to trophic interactions in the present analyses. Our food webs showed that most predators within the study area feed on multiple prey species (Figures 1 and 2), thus reducing the likelihood of detecting trophic interactions due to dietary plasticity (Robinson et al, 2023; Thurman et al, 2019). Some trophic interactions may not be described in the literature and are subsequently categorised as non-trophic interactions in our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a small proportion of co-occurrences were attributable to trophic interactions in the present analyses. Our food webs showed that most predators within the study area feed on multiple prey species (Figures 1 and 2), thus reducing the likelihood of detecting trophic interactions due to dietary plasticity (Robinson et al, 2023; Thurman et al, 2019). Some trophic interactions may not be described in the literature and are subsequently categorised as non-trophic interactions in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The North Sea represents a "wasp-waist" system, where a few key forage fish species, i.e., sandeels (Ammodytes spp. ), herring and sprat (clupeids), exert control over the abundance of predators, i.e., marine mammals, predatory fishes, seabirds, through bottom-up interactions, and control the abundance of zooplankton prey through top-down interactions (Fauchald et al, 2011;Lynam et al, 2017;Robinson et al, 2023). The abundance and quality of sandeels, the dominant bait fish in the North Sea, has, however, been declining in recent decades, contributing to failures in seabird breeding (MacDonald et al, 2019;Wanless et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed temporal trends in the community through partitioning the data by sampling month, and spatial trends by dividing the samples into categories based on their distance from shore; near (<1.2 km), middle-near (between 2.5 and 7 km), middle-far (between 7 and 10 km), and far (> 10 km up to 16.1 km) (Drummond et al, 2021;Fraija Fernández et al, 2020). These categories were defined based on previous observations that juvenile minke whales were most frequently sighted inshore (<2.5 km), whilst adults more frequently occurred further offshore (>10 km) (Robinson et al, 2023).…”
Section: Community Analysismentioning
confidence: 99%
“…The dominant minke whale prey species, such as sandeels and clupeids, were the most abundant vertebrate species detected with our primer sets (Figure 3). Abundances vary throughout the foraging season which would account for the dietary plasticity exhibited by these whales (Robinson et al, 2023). Sandeels were most abundant during June and July, when they are foraging in the water column, but declined from August onwards, when they return to burrows in the sediment (Henriksen et al, 2021) (Figure 2.5).…”
Section: Minke Whale Habitat Use In Relation To Prey Speciesmentioning
confidence: 99%